Desigualdades sociales y acceso a los servicios de salud: determinantes que condicionan la equidad sanitaria en América Latina - Luis Raúl Chapa Mejía (Imperium Académico Multidisciplinary Journal, 2026)
Social inequalities constitute a structural challenge to ensuring equitable access to health services in Latin America, owing to the interaction of socioeconomic, geographical, educational, occupational, cultural and institutional factors that create unequal opportunities for accessing care. Although the expansion of coverage and the strengthening of health systems have brought about significant progress, barriers persist that particularly affect low-income populations, people living in rural, peripheral or geographically isolated areas, and groups with limited social protection. The research analysed social inequalities and the socioeconomic, geographical, cultural and institutional determinants that influence access to health services and shape health equity in Latin America. A quantitative approach with a descriptive scope was adopted through a systematic documentary review in accordance with the PRISMA method, aimed at identifying and characterising scientific publications related to the variables analysed. The findings showed that economic and geographical conditions represented the main constraints on timely and continuous access to health services, while educational, occupational, cultural and institutional barriers intensified existing difficulties. It was concluded that the interaction of these determinants significantly influenced health equity across the region.